Racial Discrimination In Law Enforcement: Challenges For Human Rights In A Multicultural Society - Indrayati, Rosita; Saputra, Calvin Yudha; Ahmada, Vaza Khulucky (Jurnal Justiciabelen, 2024)
This essay explores the important issue of racial discrimination in law enforcement and its challenges to human rights in a multicultural society. First, this research analyzes the root causes of racial discrimination in law enforcement. Sometimes, racial bias, stereotypes, and prejudice play a role in police and court decisions. These factors are often rooted in deep history, culture, and social structures. Therefore, a deeper understanding of how these biases develop is key to overcoming this problem. Second, this essay describes the impact of racial discrimination on a multicultural society. Inequality in law enforcement creates distrust of the legal system, which can result in social tensions and feelings of insecurity. Racial discrimination can also hinder social mobility and opportunity for individuals from minority groups. Third, this essay explores the efforts that have been made to overcome racial discrimination in law enforcement. This includes policy changes, better police training, and efforts to increase the accountability of law enforcement agencies. Additionally, a more holistic approach involves public education about the importance of human rights and cooperation between multicultural communities to combat discrimination. Through an in-depth understanding of the root causes, impacts, and efforts to overcome racial discrimination in law enforcement, this essay contributes to stronger awareness and advocacy to ensure that human rights are respected equally in multicultural societies.